Functional Head Impulse Testing Might Be Useful for Assessing Vestibular Compensation After Unilateral Vestibular Loss - Sjögren, Julia; Fransson, Per-Anders; Karlberg, Mikael; Magnusson, Måns; Tjernström, Fredrik (Frontiers in Neurology, 2018)
Background: Loss of the vestibuloocular reflex (VOR) affects visual acuity during head movements. Previous studies have shown that compensatory eye-saccades improve visual acuity and that the timing of the saccade is important. Most of the tests involved in testing VOR are made with passive head movement, that do not necessarily reflect the activities of daily living and thus not being proportionate to symptoms and distresses of the patients. Objective: To examine differences between active (self-generated) or passive (imposed by the examiner) head rotations while trying to maintain visual focus on a target. Method: 9 patients were recruited (4 men and 5 women, mean age 47) and tested with video Head Impulse Test (vHIT) and Head Impulse Testing Device – Functional Test (HITD-FT) during passive and active movements while looking at a target. VOR gain, latencies of covert saccades, frequency of covert saccades and visual acuity were measured and analysed. Results: Active head-impulses towards the lesioned side resulted in better visual acuity (p=0.002) compared to conventional passive head-impulses and generated eye-saccades with significantly shorter latencies (p=0.004). Active movements to the lesioned side generated dynamic visual acuities that were as good as when testing the intact side. Conclusion: Actively generated head impulses resulted in normal dynamic visual acuity, even when performed towards the side of total vestibular loss. This might be attributed to the appearance of short-latency covert saccades. The results show a strong relationship between self-generated movements, latencies of covert saccades and outcome in HITD-FT, i.e. a better dynamic visual function with less retinal slip which is the main function of the VOR. The method of active HITD-FT might be valuable in assessing vestibular compensation and monitoring ongoing vestibular rehabilitation.